1973
DOI: 10.1037/h0034198
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sex-role stereotypes on evaluations of male and female supervisory behavior.

Abstract: This investigation examined the way sex-role stereotypes-perceptions and expectations of what is appropriate behavior for males and females-influence evaluations of male and female supervisory behavior. Undergraduate students and bank supervisors were asked to read one of six versions of a supervisory problem (with either a male or female supervisor and with either male, female, or mixed subordinates) and to evaluate the effectiveness of four supervisory styles. Results indicated that sex-role stereotypes do i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
6
3

Year Published

1975
1975
2002
2002

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(120 citation statements)
references
References 6 publications
4
107
6
3
Order By: Relevance
“…As in the résumé experiments that we discussed above, the characteristics of stimulus persons other than their sex were held constant, and their sex was varied. Although the majority of these experiments presented written vignettes describing leaders' behavior (e.g., Rosen & Jerdee, 1973), some of the experiments presented male and female confederates who had been trained to lead research participants in particular styles (e.g., D. M. Lee & Alvares, 1977). The samples of evaluators in these experiments consisted primarily of undergraduate students but included high school students and graduate students as well as managers and other employees.…”
Section: Goldberg-paradigm Experiments On Evaluations Of Leadersmentioning
confidence: 99%
“…As in the résumé experiments that we discussed above, the characteristics of stimulus persons other than their sex were held constant, and their sex was varied. Although the majority of these experiments presented written vignettes describing leaders' behavior (e.g., Rosen & Jerdee, 1973), some of the experiments presented male and female confederates who had been trained to lead research participants in particular styles (e.g., D. M. Lee & Alvares, 1977). The samples of evaluators in these experiments consisted primarily of undergraduate students but included high school students and graduate students as well as managers and other employees.…”
Section: Goldberg-paradigm Experiments On Evaluations Of Leadersmentioning
confidence: 99%
“…We can only speculate on the explanation for these findings Researchers have thoroughly documented the influence of sex stereotypes on a range of managerial selection, promotion, and compensation decisions (e.g., Gerdes & Gerber, 1983, Rosen & Jerdee, 1973, 1974Rosen & Mende, 1979). Perhaps sex stereotypes regarding what various male and female jobs are worth influenced choices among options for coping with labor shortages Recent research by Grams and Schwab (1985) illustrates how knowledge about the current market wage for a position influences the number of job evaluation points assigned to that position.…”
Section: Discussionmentioning
confidence: 99%
“…In Business as Investigated by Jerdee In 1973 and Rosen and Jerdee reported the following four studies.…”
Section: The Differential Evaluation Of Men and Womenmentioning
confidence: 99%
“…Shaw (1972) found that 132 college recruiters attributed significantly more positive adjectives to a male applicant for a management training program than to a female applicant even though both applicants were simply described as having Master of Business Administration degrees in management theory and policy. Of particular Interest, however, is a series of four survey-experiments conducted by Rosen and Jerdee (1973, 1974a, 1974b, 1974c. In brief, these studies Indicate that both male and female college students and executives tend to perceive, evaluate, and reward men and women in business situations quite differently even though this tendency does not appear to be quite as great among female managers as it is among their male colleagues.…”
Section: Behavioral Implications Of Attitudesmentioning
confidence: 99%
See 1 more Smart Citation